2001
DOI: 10.2214/ajr.177.4.1770823
|View full text |Cite
|
Sign up to set email alerts
|

MR Colonography Without Colonic Cleansing

Abstract: Fecal tagging obviates bowel cleansing and should, therefore, enhance patient acceptance for MR colonoscopy. Barium used as the tagging agent is promising because it is inexpensive, commercially available, and characterized by an excellent safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Pappalardo et al [19] showed that MRC was associated with similar diagnostic accuracy for diagnosing colonic endoluminal lesions compared with conventional colonoscopy. Lauenstein et al [20,21] indicated that barium-tagged MRC was promising for detecting all lesions more than 8 mm in diameter. Luboldt et al [22] found that MRC was promising for filtering out individuals with obvious colorectal mass lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Pappalardo et al [19] showed that MRC was associated with similar diagnostic accuracy for diagnosing colonic endoluminal lesions compared with conventional colonoscopy. Lauenstein et al [20,21] indicated that barium-tagged MRC was promising for detecting all lesions more than 8 mm in diameter. Luboldt et al [22] found that MRC was promising for filtering out individuals with obvious colorectal mass lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal tagging is a concept based on altering the signal intensity of stool by adding contrast modifying substances to regular meals such as barium sulfatecontaining contrast agent (33,(63)(64). This has been shown to decrease the signal intensity of stool in T1-weighted images because of the extended relaxation time.…”
Section: Dark-lumen Mrc With Fecal Taggingmentioning
confidence: 99%
“…Thus, fecal tagging may render stool virtually indistinguishable from the distending rectal enema on MR images. The fecal tagging based MRC was applied successfully in a volunteer study (63). However it has shown a poor diagnostic accuracy and poor acceptance in a patient study (64).…”
Section: Dark-lumen Mrc With Fecal Taggingmentioning
confidence: 99%